The effect of poverty on developmental screening scores among infants - Giselle Souza de Paiva; Ana Cláudia Vasconcelos Martins de Souza Lima; Marília de Carvalho Lima; Sophie Helena Eickmann (2010)
CONTEXT AND OBJECTIVE: Child development is negatively influenced by multiple risk factors associated with poverty, thus indicating the importance of identifying the most vulnerable groups within populations that are apparently homogeneous regarding their state of socioeconomic deprivation. This study aimed to identify different levels of poverty in a population of low socioeconomic condition and to ascertain their influence on infants' neuropsychomotor development. DESIGN AND SETTING: Cross-sectional study conducted at four Family Health Units in the Health District IV in the city of Recife, Brazil. METHODS: The sample comprised 136 infants aged 9 to 12 months, which represented 86% of all the infants in this age group, registered at the units studied. Socioeconomic status was assessed through a specific index and child development through the Bayley III screening test. RESULTS: Around 20% of the families were in the lowest quartile of the socioeconomic level index and these presented the highest frequency of infants with suspected delay in receptive communication. Maternal and paternal unemployment negatively influenced receptive communication and cognition, respectively. Not possessing a cell phone (a reflection of low socioeconomic status) was associated with worse cognitive performance and gross motricity. Male infants showed a higher frequency of suspected delay in receptive communication. CONCLUSIONS: Infants of more precarious socioeconomic status more frequently present suspected developmental delay. Development monitoring and intervention programs should be encouraged for this subgroup, thereby providing these children with a better chance of becoming productive citizens in the future.